The Theocentric Worldview: Sustainability Education for Religion and Spiritual - Muhamad, Mohd Mokhtar; Syed Abdullah, Sharifah Intan Sharina; Mohamad Arsad, Nurazidawati (SCAD Independent, 2021)
Several recent studies started to relate religious beliefs and sustainable behavior. For this reason, there is a high possibility that students’ religious beliefs can be a strong impetus for practicing sustainability knowledge. The education for sustainable development (ESD) in universities should not be separated from the meaningful religious belief of university students. Therefore, we proposed the theocentric worldview which centered on a religion-spiritual relationship with God to be included as a part of ESD. This worldview is important in making ESD content meaningful for religious university students. In this paper, we used a religion-spiritual concept from Islamic teachings as an example of how a religious belief can be embedded within ESD for university students.